Resilience in the Malawi agri-food system amid the COVID-19 crisis: Evidence from a 2021 nationally representative household survey - Ragasa, Catherine; Balakasi, Kelvin; Carrillo, Lucia (International Food Policy Research Institute, 2022)
This report provides a farm-level analysis of the effects of the COVID-19 crisis, 12–15 months in, using a nationally representative rural household survey conducted in June–July 2021. We draw three major observations from the survey. First, farming activities, access to inputs and extension services, production, and sales were largely unaffected by the crisis. There were temporary challenges in accessing inputs during lockdown and mobility restrictions, and input prices and transportation costs increased; however, production and sales volume and value were largely unaffected. Second, although farming was not affected, other nonfarm livelihoods of a large proportion of farmers were negatively affected because of lower demand and fewer buyers. Eighty-two percent of rural households were engaged in various nonfarm livelihoods, and 32 percent reported negative impacts of the crisis on their nonfarm incomes. Third, direct responses from sample households indicate no negative impacts of the crisis on food access and food consumption by most rural households. Comparisons between 2018 and 2021 of various food security indicators show improvements in food access and dietary diversity. Improvements are likely attributable to better harvests overall and greater awareness of the need to eat healthy and nutritious foods to combat COVID-19 and other diseases. Results show overall resilience of rural households and the agriculture sector amid the COVID-19 crisis. Nonetheless, the survey was conducted right after harvest, and the situation needs to be monitored during the lean season.